Trading under Market Impact: Crossing Networks Interacting with Dealer Markets - Jana Bielagk; Ulrich Horst; Santiago Moreno-Bromberg (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
We use a model with agency frictions to analyze the structure of a dealer market that faces competition from a crossing network. Traders are privately informed about their types (e.g. their portfolios), which is something the dealer must take into account when engaging his counterparties. Instead of participating in the dealer market, the traders may take their business to a crossing network. We show that the presence of such a network results in more trader types being serviced by the dealer and that, under certain conditions, the bookś spread shrinks. We allow for the pricing on the dealer market to determine the structure of the crossing network and show that the same conditions that lead to a reduction of the spread imply the existence of an equilibrium book or crossing network pair.
Keywords: D42; D53; G12; G14; 330; asymmetric information; crossing networks; dealer markets; non-linear pricing; principal-agent games